Low-Voltage Wide-Bandwidth CDBA and Its Application to Current-Mode Ladder Filters - Tangsnrat, Worapong; Patthananurak, Phakamard; Surakampontorn, Wan lop (Engineering and Applied Science Research, 2015)
In this paper, a design of.current differencing buffered amplifier (CDBA) for low-voltage applications is presented. The proposed CDBA is simple and is designed to operate with a minimum power supply of 2 volts. The PSPICE simulation results demonstrating the circuit performance are included. Some design procedures using this CDBA as an active element in the leapfrog simulation of high frequency current mode ladder filters are also introduced.